Novel deleterious sequence change in the NLRP12 gene in a child with autoinflammatory syndrome, joint hypermobility and cutis laxa from India. - Kanjaksha Ghosh; Kanchan Mishra; Avani Shah; Parizad Patel; Shrimati Shetty (Mediterranean Journal of Hematology and Infectious Diseases)
An otherwise healthy male child of 9 years presented with paroxysmal fever and diffuse abdominal pain along with loss of appetite and nausea lasting for 3-4days every 4-6 weeks for last 2 years. He also has stretchable skin and hypermobile joint which he inherited from his mother who never suffered any paroxysmal attack of the kind.  Work up for acute intermittent porphyria, lead poisoning and familial mediterranean fever was negative. A novel harmful sequence change in NLRP12 gene was detected and a diagnosis of NLRP12 associated autoinflammatory syndrome was made. This sequence change with disease has not yet been reported in the literature and is the first such case of NLRP12 related autoinflammatory syndrome from India.